Policies for the immunization against serogroup B meningococcus for adolescents immunized during the first two years of life: A mini review - Claudia Palmieri; Lorenza Moscara; Silvio Tafuri; Pasquale Stefanizzi (Human Vaccines & Immunotherapeutics)
Two vaccines are available to prevent serogroup B meningococcal disease, i.e. the four-component meningococcal serogroup B vaccine (4CMenB) and the bivalent-factor-H-binding-protein meningococcal serogroup B vaccine (MenB-fHbp). Currently, 4CMenB is offered as part of routine infant immunization schedules. Available immunogenicity data showed a progressive decline in protective serum bactericidal antibodies (SBA) titers, with a re-enhancement following a booster dose during infancy. Responses did not seem to be long-lasting and vaccinated individuals might be at risk of meningococcal diseases duriṇg adolescence. Only one study evaluated the possibility to administer a single booster dose to immunocompetent adolescents who received a primary series during infancy. Despite a high proportion of enrollees achieving protective SBA levels 28 days post-booster, titers tended to decrease 1 year after. Immunocompetent adolescents who received a primary series and a booster during the first two years of life might rather benefit from re-vaccination against MenB; current evidence does not support the possibility of a booster.